AVALIATION OF SPECIES OF Paspalum under grazing AVALIAÇÃO DE ESPÉCIES DE Paspalum SOB PASTEJO - Milena Provazi; Patrícia de Menezes Santos; Luiz Alberto Rocha Batista; Ciniro Costa; Paulo Roberto de Lima Meirelles (Ciência Animal Brasileira, 2008)
The objective of this experiment was to verify the outcome of the grazing above the productivity and the persistence of three accesses of Paspalum. The experiment was developed on Southeastern Cattle Embrapa, in São Carlos, SP, in the period of January to December 2005. Three genotypes of Paspalum (Paspalum. Guenoarum – BRA-006572, Paspalum malacophyllum - BRA-003077 and Paspalum atratum – BRA-011681) and two controls (Brachiaria decumbens and Paspalum atratum cv. Pojuca) were compared under two grazing intensities (1500 and 3000 kg MS/ha of post-graze residue). Plots were mob grazed (1-day grazing followed by 27-day rest (water period) and 1-day grazing followed by 55-day rest (dry period) and stocking rate was adjusted according to the herbage mass available and the treatment grazing intensity. The following variables have been evaluated: total herbage mass before and after grazing; proportion of leaf, stem and dead material; occurrence of weeds and tiller density and occurrence of diseases and symptoms of mineral toxicity or deficiency. For both grazing intensities the Paspalum atratum demonstrated positive characteristics of production and persistence indicating that these are promising genotypes for use in intensive systems of pasture. KEY WORDS: Intensity of grazing, pasture, production of forage, tillers. Desenvolveu-se o experimento na Embrapa Pecuária Sudeste, localizada em São Carlos, SP, no período de janeiro a dezembro de 2005, objetivando verificar o efeito do pastejo sobre a produtividade e a persistência de três acessos de Paspalum (Paspalum guenoarum – BRA-006572, Paspalum malacophyllum – BRA-003077 e Paspalum atratum – BRA-011681) comparados com duas testemunhas (Brachiaria decumbens e Paspalum atratum cv. Pojuca), em dois níveis de desfolha (1.500 e 3.000 kg MS/ha de resíduo pós-pastejo). O ensaio foi do tipo mob grazing, em que se utilizou o método de pastejo rotacionado com 27 dias de descanso e um dia de ocupação (período das águas) e 55 dias de descanso e um dia de ocupação (período das secas). Ajustou-se a taxa de lotação animal das parcelas de acordo com a massa de forragem disponível antes do pastejo e com o nível de desfolha previsto pelos tratamentos. As variáveis foram: massa de forragem antes e após o pastejo; proporções de folhas, hastes e material morto; densidade de perfilhos; incidência de plantas invasoras; observações relativas à susceptibilidade a pragas e doenças, sintomas de toxidez e deficiência mineral. O Paspalum atratum BRA-011681 apresentou características positivas de produção e persistência, tanto na altura de pastejo de 0,15 m como na de 0,30 m, evidenciando que essa espécie é promissora para uso em sistemas intensivos de pastejo. PALAVRAS-CHAVES: Intensidade de pastejo, pastagem, perfilhos, produção de forragem.